The Timing of T Cell Priming and Cycling - Obst, Reinhard (Frontiers in Immunology, 2015)
The proliferation of specific lymphocytes is the central tenet of the clonal selection paradigm. Antigen recognition by T cells triggers a series of events that produces expanded clones of differentiated effector cells. TCR signaling events are detectable within seconds and minutes and are likely to continue for hours and days in vivo. Here, I review the work done on the importance of TCR signals in the later part of the expansion phase of the primary T cell response, primarily regarding the regulation of the cell cycle in CD4+ and CD8+ cells. The results suggest a degree of programming by early signals for effector differentiation, particularly in the CD8+ T cell compartment, with optimal expansion supported by persistent antigen presentation later on. Differences to CD4+ T cell expansion and new avenues towards a molecular understanding of cell cycle regulation in lymphocytes are discussed.